The course social work Unespar / Campus Apucarana: a study of the profile of their graduates - Martins, Julio Cesar (2020)
The objective of this article is to present the profile of the graduates of the Social Service course at Unespar / Campus Apucarana graduated in the period from 2005 to 2017, considering socioeconomic aspects, academic training, professional and work conditions, in addition to reflecting on the profile of professional that the course proposes to train. The methodological proposal is based on a qualitative approach of an exploratory nature, using field research through the sending of an electronic questionnaire. Considering that the university does not have a database of graduates, it is believed that the data collection can contribute to discussions in the Social Work course. Furthermore, the article highlights the need to create an egress portal on the institutional website.